AKTIVITAS AMILASE UBI JALAR (Ipomoea batatas Lam.) VARIETAS MELATI PADA BERBAGAI pH DAN SUHU - , SWASTI CANDRIKA PUTRI; , Dr. Ir. M. Nur Cahyanto, M. Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The purposes of this study were to determine the effect of pH and temperature to the activity and stability of sweet potatoâs amylase enzyme. Sweet potato was extracted using cold distilled water to obtain the supernatant as a source of crude enzyme. The crude enzyme was stored at 4ÂºC. The activity tests were carried out at various pHs (3